Molecular analysis of linezolid resistance in clinical Enterococcus faecium isolates by polymerase chain reaction and pyrosequencing - Schnitzler, Paul; Schulz, K.; Lampson, Christian; Geiss, M.; Geiss, Heinrich K. (European journal of clinical microbiology & infectious diseases, 2011)
Resistance to linezolid has been associated with a G2576T mutation in the 23 S rRNA gene. Clinical isolates of linezolid-sensitive and linezolid-resistant vancomycin-resistant Enterococcus faecium of a liver transplant patient have been analysed for the G2576T mutation by polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP), conventional sequencing and pyrosequencing. A clear association between the number of mutated 23 S rRNA genes and the level of linezolid resistance has been demonstrated. Linezolid susceptibility re-emerged after cessation of linezolid therapy; however, the re-initiation of linezolid therapy resulted in the re-emergence of linezolid-resistant strains. Pyrosequencing rapidly detected the number of mutated alleles and is superior to conventional PCR-RFLP for the detection of heterozygous mutations.
Published: 03 September 2010
Gesehen am 25.10.2022